2022
DOI: 10.3310/rlcf6332
|View full text |Cite
|
Sign up to set email alerts
|

Moulded cast compared with K-wire fixation after manipulation of an acute dorsally displaced distal radius fracture: the DRAFFT 2 RCT

Abstract: Background Patients with a displaced fracture of the distal radius are frequently offered surgical fixation. Manipulation of the fracture and moulded plaster casting is an alternative treatment that avoids metal implants, but evidence of its effectiveness is lacking. Objective To compare functional outcomes, quality-of-life outcomes, complications and resource use among patients with a dorsally displaced fracture of the dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…24 Furthermore, previous studies have shown that there are negligible changes in radiological measurements between six weeks and 12months following injury. 10 Therefore, it was not considered ethical to ask participants to have further radiographs taken after six weeks for the purposes of this study. A final important point of note is that one in eight participants treated with a moulded plaster cast as part of the DRAFFT2 trial lost fracture reduction in the first two weeks following their manipulation and required subsequent surgical fixation of their fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, previous studies have shown that there are negligible changes in radiological measurements between six weeks and 12months following injury. 10 Therefore, it was not considered ethical to ask participants to have further radiographs taken after six weeks for the purposes of this study. A final important point of note is that one in eight participants treated with a moulded plaster cast as part of the DRAFFT2 trial lost fracture reduction in the first two weeks following their manipulation and required subsequent surgical fixation of their fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited as part of the DRAFFT2 trial. 10 The analysis described here was pre-planned as part of the trial protocol. The protocol, analysis plan, and clinical and health economic data from the trial have been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…This large, multicentre randomized controlled trial from Oxford (UK) set out to compare the outcomes of patients with a dorsally displaced fracture of the distal radius, treated with manipulation and surgical fixation with Kirschner (K)-wires, with those treated using manipulation and a moulded cast. 4 The primary outcome measure reported here was the Patient-Rated Wrist Evaluation (PRWE) score at 12 months. In total, 500 participants (mean age 60 years, 83% female) were randomly allocated to receive a moulded cast (n = 255) or surgical fixation with K-wire (n = 245) following manipulation of their fracture.…”
Section: Moulded Cast Compared With Kirschner Wire Fixation After Man...mentioning
confidence: 99%